Kesulitan Pembelajaran Matematika Siswa Kelas VI SD Negeri 04 Lubang Buaya - Ar-rizky Maulana Akbar; Wibisono F B (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research seeks to identify the sources and locations of arithmetic learning challenges related to integer counting operations. Class VI, which is the focus of this study, has an average math score that is lower than the KKM. Methods such as tests, observations, and interviews are used to gather data. Students' mastery of the topic of whole number counting operations was assessed using the test technique, which consisted of a 10-question essay. Finding out how the subject is doing during math learning activities and what variables could influence math learning are both accomplished via the use of the observation technique. The purpose of the interview was to get a clear understanding of the challenges that students have while studying the content for integer counting operations. Fifty percent of students had trouble with skills, 23.3% had trouble with ideas, and 20% had trouble with problem solving, according to the data from the final analysis. This includes students in the adequate group. Teachers are encouraged to shape mathematics teaching patterns based on more than just pupils' problem-solving abilities. More significant, however, is figuring out how to encourage pupils to comprehend and fully grasp current ideas so that they do not have any trouble understanding mathematics.